Recognition of Machined Features from Solid Database of Prismatic Components - Ismail, Napsiah; Abu Bakar, Nooh (Universiti Putra Malaysia Press, 1997)
The automation of process planning requires features to he recognized directly from a computer aided design (CAD) system. This paper presents a new technique for recognition of machined features using point classification technique with a logic-based approach. Boundary r~presentation of solid modelling is used to model a prismatic component. The system is developed entirely in the AutoCAD environment, and the AutoLISP language was used to build the recognition system as it has direct access to the database. Test results are presented to demonstrate the capabilities of the feature recognition algorithm. This paper concentrates on depression and protrusion type machined features.